THE PROBLEMS OF MEASUREMENT THE HIGHER PROFESSIONAL EDUCATION INSTITUTIONS EFFICIENCY - L. M. Nurieva; S. G. Kiselev (Образование и наука)
The aim of the article is to analyze the results of monitoring efficiency of universities by the example of educational institutions of the Omsk region.Methods. The methodology of complex research, including methods of statistical, sociological, comparative analysis and analysis of documents and databases of the Ministry of Education and Science and educational organizations are applied.The results and scientific novelty. It is found that the evaluation of higher education institutions depends not so much on the success of their work as on the list of used measurement indicators and features of scoring system. Rejection of a comprehensive study of the work of educational institutions, reflected in the use of individual evaluation indicators, leads to a substitution of the object of measurement and incorrect results of the survey.Practical significance. The authors suggest that the findings undertaken by them will lead to timely and strategic university work correction: contribute to the adjustment of the methods of evaluation of higher education institutions and improve their adequacy problem of a comprehensive study of the work of universities.